Hospital-Associated Outbreak of Middle East Respiratory Syndrome Coronavirus: A Serologic, Epidemiologic, and Clinical Description - Al-Abdallat, Mohammad Mousa; Payne, Daniel C.; Alqasrawi, Sultan; Rha, Brian; Tohme, Rania A.; Abedi, Glen R.; Al Nsour, Mohannad; Iblan, Ibrahim; Jarour, Najwa; Farag, Noha H.; Haddadin, Aktham; Al-Sanouri, Tarek; et al. (Clinical infectious diseases, 2014)
Background. In April 2012, the Jordan Ministry of Health investigated an outbreak of lower respiratory illnesses at a hospital in Jordan; 2 fatal cases were retrospectively confirmed by real-time reverse transcription polymerase chain reaction (rRT-PCR) to be the first detected cases of Middle East respiratory syndrome (MERS-CoV). Methods. Epidemiologic and clinical characteristics of selected potential cases were assessed through serum blood specimens, medical record reviews, and interviews with surviving outbreak members, household contacts, and healthcare personnel. Cases of MERS-CoV infection were identified using 3 US Centers for Disease Control and Prevention serologic tests for detection of anti–MERS-CoV antibodies. Results. Specimens and interviews were obtained from 124 subjects. Seven previously unconfirmed individuals tested positive for anti–MERS-CoV antibodies by at least 2 of 3 serologic tests, in addition to 2 fatal cases identified by rRT-PCR. The case-fatality rate among the 9 total cases was 22%. Six subjects were healthcare workers at the outbreak hospital, yielding an attack rate of 10% among potentially exposed outbreak hospital personnel. There was no evidence of MERS-CoV transmission at 2 transfer hospitals having acceptable infection control practices. Conclusions. Novel serologic tests allowed for the detection of otherwise unrecognized cases of MERS-CoV infection among contacts in a Jordanian hospital-associated respiratory illness outbreak in April 2012, resulting in a total of 9 test-positive cases. Serologic results suggest that further spread of this outbreak to transfer hospitals did not occur. Most subjects had no major, underlying medical conditions; none were on hemodialysis. Our observed case-fatality rate was lower than has been reported from outbreaks elsewhere.